A complete science-teaching activity from planning to evaluation - Pacis, Jose B (1974.)
The objective of this paper is to provide only a framework of information to which the teacher may, as the years go by, add the necessary amount of "flesh" in order to complete and round out his skill in teaching science to the young. The best way to show how this is done is through a model or example. We will, therefore, try to go through the entire process wherein one complete teaching activity is (1)planned, (2) prepared, (3) conducted and (4) evaluated. Planning. "Planning involves the following sequence of activity: 1. Formulate your course of study if a satisfactory one is not already available or if you prefer to make your own; 2. Select your topic for the day from such course of study; 3.Formulate the relevant behavioral objectives. The relevant steps are : a. Identify the final instructional objective by name; b.Determine the kind of observable behavior that will be accepted as evidence that the learner has achieved the objective; c. Define this behavior further by describing the important conditions (if such are desired) under which the behavior is expected to occur. (Such conditions or restrictions could be one or more of the following: given a list of ...; given a standard set of tools ...; without the aid of references ...; etc); d. Specify the criteria of acceptable performance by describing to be considered acceptable. (Such as: within 15 minutes ...; must be 85% accurate ...; etc.); 4. Determine the corresponding teaching activity. Write your laboratory Activity Plan to include the following: a. Laboratory Activity Plan Number. b. Proposed date of the activity. c. Topic (or title). d. Objective/objectives. e. Procedure (laboratory Instruction sheet). f. Materials. i. To be supplied by the school. ii. To be supplied by the students. g. Pre-lab discussion. i. Explain materials, equipment to be used, others. ii. Procedure. iii. Precautions. iv. Deadline for finishing. v. Others. h. The activity proper. i. Post-Lab Discussion. i. Discuss results; reach a consensus. ii. Generalizations, inferences expected from such results of activity. iii. Questions to ask; concepts to elicit. iv. Practical uses of knowledge obtained if any. j. Evaluation (only if convenient). Describe the process of evaluation to be used. k. Write out possible examinations questions concerning this topic for future use (optional but very advisable at this point since the objective and the activity plan are still fresh in your mind and the writing of such examination questions would come to the surface so much more readily at this time). We follow the following steps under "Preparation": 1. Refer to your list of materials and assemble all of them together; give the necessary assignment (if any) to your students. 2. Perform the experiment to test whether any modification of your plan is needed and to find out whether your procedure is reliable or not; time your experiment. 3. Modify your plan/procedure/condition/list of materials/ equipment/precautions/etc. according to your experience during the dry run. 4. Re-write your possible test questions if you have prepared any. Executing the Plan. Here are some pointers to help you conduct the activity more successfully. Most, if not all, are already known to you. 1. Pause before you start - until full attention from the class is obtained. 2. Use motivation whenever needed or useful. 3. Know your students by observing and listening to them. 4. Where experiments are inadequate, use analogy. 5. make use of pertinent and useful stories for additional interest. 6. Do not forget to use the chalk and board at every turn and opportunity. 7. Develop a circulation pattern in supervising the laboratory activity; as far as possible, never turn your back to any portion of the class while you go through your rounds. 8. Do not get pinned down by a single student; your responsibility is towards a whole class. 9. do not interrupt or disturb the laboratory activity once it is started. 10. Do not interfere with the activity; refrain from handling instruments. 11. Noise is expected in a laboratory activity but it should be reasonable and at all times under control. 12. Student groupings should be reshuffled periodically and whenever there is need. 13. Promote intellectual honesty. 14. Throw back any questions from the class. 15. Elicit answers to questions whenever possible. 16. If no one including the teacher can give the correct answer to a questions, let the teacher admit that he does not know but promise to look it up or to consult others for the class. The class could be also be asked to make a research work on this. 17. When asking questions, give a neutral response to the answers and try to let as many other students as possible answer the same question. Play the game. 18. Questions should be so framed and sequenced as to lead the students eventually to the right answer. 19. Do not forget to mention practical applications of subjects under study whenever this is possible. 20. make extensive use of tables and graphs and teach the students to be able to prepare their own tables and graphs. 21. Inject humor into your teaching. You will find it stimulating-and thoroughly helpful. The functions of evaluation are: 1. As feedback to the learner. 2. As feedback to the teacher. 3. As reinforcement. 4. As basis for decisions about the learner. 5. Information for administrative judgements and decisions. We are interested in the first four (4) in relation to our evaluation of the teaching-learning activity and we have two common ways of doing this; the oral and the written test. The oral test is undesirable for many reasons but much of its weakness is solved by its integration with the process approach type of post-lab discussion. As an inherent part of the post-lab discussion, specially if an Oral Discussion Grading Sheet is made use of, the "oral test" element in the post-lab discussion can become even more useful indeed as a form of evaluation. Because of unavoidable inadequacies of the oral test, however, the more reliable objective type written test is the preferred instrument for instructional evaluation. The steps in written test construction are: 1. Write down the principal behavioral objectives of the chapter or unit which you wish evaluated. 2. Prepare a Table of Specifications. 3. Write your test questions accordingly. Strive for a balanced distribution of questions corresponding to each objective according to their relative importance. after administering the test and correcting the same, make a tally of the scores. Solve for the standard deviation and for the mean according to the easy way by using Table S and Table R. Draw the curve of the class performance. Assign the grades you wish to attach to the scores which are one standard deviation above and below the mean. Locate the point corresponding to them on the Score-Grade Graph and draw a line described by these two points. Find on the graph the corresponding grades to all other scores made by your students with the aid of this line drawn. Finally, re-examine the results of your test by subjecting each test item to analysis for its index of difficulty and for its discrimination index. In general, one may be satisfied with a difficulty index of from 0.5 to 0.8 and a discrimination index of from 0.4 to 1.00.
Seminar Paper (Graduate, Master of Arts in Teaching Chemistry) College of Education, Graduate School, University of the Philippines.
Keywords: Chemistry -- Methods of Teaching